Upaya Peningkatan Kualitas UMKM Busana Ritual Medan - Elserra Siemin Ciamas (Cattleya Darmaya Fortuna, 2022)
The limited resources of UMKM Busana Ritual such as the number of skilled staff, materials, etc. are one of the problems in Busana Ritual. High demand but in the process takes quite a long time. Materials for robes are often returned due to quality mismatches, causing delays in the production process. This causes the quality of Busana Ritual to fluctuate in the face of the market. The purpose of this service is intended for Busana Ritual owners to find out the benefits of the marketing mix, which is very influential in the continuity of a business, such as the implementation of 7P, STP, HPP and SWOT Analyze. (Maisah et al., 2020) The application of marketing strategy is intended as a process to develop, and maintain a strategic fit between the objectives and capabilities of the institution, as well as changing marketing opportunities. This Community Service is intended to provide motivation and solutions for Busana Ritual. The method used is to explain the benefits of Marketing Research and how to determine 7P, STP, HPP and SWOT Analyze. The socialization session was in the form of an interview about the material presented. As well as evaluating Busana Ritual such as products, resources, etc. The results of the service carried out in the Busana Ritual are to see the obstacles in the Busana Ritual, so that solutions are found, as well as to improve the quality of the Busana Ritual